Strong Association between Serological Status and Probability of Progression to Clinical Visceral Leishmaniasis in Prospective Cohort Studies in India and Nepal - Hasker, Epco; Malaviya, Paritosh; Gidwani, Kamlesh; Picado, Albert; Ostyn, Bart; Kansal, Sangeeta; Singh, Rudra Pratap; Singh, Om Prakash; Chourasia, Ankita; Singh, Abhishek Kumar; Shankar, Ravi; Wilson, Mary E.; et al. (PLOS Neglected Tropical Diseases, 2014)
Author Summary To study the association between positive serology for VL among asymptomatic persons and progression to disease, we analyzed combined data from two different cohort studies in which over 32,000 subjects were enrolled. All subjects were screened for presence of antibodies to L. donovani with DAT and rK39. After an interval of 6–12 months, a second round of surveys was conducted in which seroconvertors were identified, i.e. persons seronegative at baseline that had become seropositive in the interval between surveys. We subdivided the subjects according to serologic titers scored as negative, moderately positive or strongly positive. During follow-up we observed that the risk of progressing to disease was not very much different between seronegative and moderately seropositive subjects, but strongly increased for high titer seropositive subjects. This pattern was true for the initial serology, and even more pronounced among seroconvertors. Given the strongly increased risk of progression to disease among those with high DAT or rK39 titers, these data raise the question whether prophylactic treatment would be beneficial. The case for prophylactic treatment would be further strengthened if it could be shown that asymptomatically infected individuals are infectious to sand flies.